SOFA score in gas-forming pyogenic liver abscess: a case series of seven patients with exploratory analysis of severity and mortality - Ning-Bo Xiao; Xiao-dong Zhang; Ze Yu; Jin-Liang Dong (Frontiers in Medicine, 2026)
Gas-forming pyogenic liver abscess (GFPLA) is a rare and highly fatal subtype of bacterial liver abscess, closely related to diabetes and hypervirulent Klebsiella pneumoniae infection. This case series analyzed seven patients diagnosed with GFPLA by CT, aiming to explore their clinical characteristics and prognosis. Among the patients, four died, with a total mortality rate of 57.1%, significantly higher than the 27.7%−37.1% reported in the literature. The sequential organ failure assessment (SOFA) scores of the deceased patients at admission were all ≥7, suggesting a potential association between higher SOFA scores and mortality in this small series. The pathogen analysis showed that 85.7% of the cases were hypervirulent Klebsiella pneumoniae infections that were positive in the latex agglutination test, and the strains were generally resistant to ampicillin but sensitive to carbapenems and enzyme-inhibitor combination preparations. In terms of treatment, only a few patients received puncture drainage, and some were unable to implement it due to coagulation dysfunction or small abscess volumes. These findings highlight the need for early identification and close monitoring of SOFA scores in patients with GFPLA, particularly those with diabetes, and suggest that a multidisciplinary approach, including effective antibiotics (e.g., carbapenems), active blood glucose control, and timely drainage, may be important for improving outcomes. However, due to the small sample size and exploratory nature of this study, observed associations should be interpreted with caution and require validation in larger cohorts.